In Search of Moderation of Islam Againts Extremism: A Promoting “Islam Pribumi” By Gus Dur - Muzayyin, Muzayyin; Kartika, Nadia Raifah Nawa; Habib, Habib (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2021)
Indonesian religious expressions are facing an extraordinary challenge with the emergence of fundamentalist movements affiliated with number of Islamic transnationalist from Middle East, which is rigidly establishing the ideology of